From statism to neo-liberalism the development process in India - Upadhyay, V. [Ed.]; Kak, Shakti [Ed.]; Barik, Kaustuva [Ed.]; Ravi Kumar, T. [Ed.] (Delhi Daanish Books, 2009)
Papers presented at a seminar organized jointly by National Committee for Celebration of Birth Centenary of Prof. D.R. Gadgil and Indian Political Economy Association.
Development thinking of Indian planners/ Kamal Nayan Kabra Productivity growth in Idian manufacturing sector: an assessment of post-liberalization period/ Kaustuva Barik Nature of investment and disparate regional growth in India: re-examining policy perspectives/ T. Ravi Kumar Trade-linked industrialization: performance and impact/ V. Upadhyay and Devashis Bose Indian agriculture in the post reform era: emerging issues and policy options/ S.P. Singh The neo-liberal policies and deepening agrarian crisis/ Shakti Kak Expenditure management/ B.P.Mathur Inter-state disparities in fiscal capacities and fiscal transfers in India/ Shibablal Meher On the margins of Indian planning/ Archana Prasad Evolution of health planning in India: a case of triumph of neo-liberalism/ Alpana Sagar
Includes index.
Includes statistical tables.
Keywords: NEOLIBERALISM; ECONOMICS; ECONOMICS -- INDIA; ECONOMIC DEVELOPMENT; ECONOMIC POLICY